The Mediating Effect of Consumer Brand Relationship Quality and Perceived Product Quality on Ethical Marketing Behavior and Brand Loyalty of Software Companies in China - ZHU, SUJUAN (Pacific International Journal, 2024)
This study examines the impact of ethical marketing practices on consumer-brand relationships, product quality perceptions, and brand loyalty within the software industry. Through a quantitative research approach, data from 352 respondents were analyzed to assess various dimensions of consumer perceptions and behaviors related to ethical marketing. Findings indicate that software companies perceived as prioritizing ethical practices benefit from stronger consumer-brand relationships, higher perceived product quality, and enhanced brand loyalty. Strategic implications suggest personalized marketing approaches, continuous product innovation, integration of ethical considerations across operations, transparent pricing strategies, and truthful communication in promotional activities as key drivers of consumer trust and loyalty.